Sistem Informasi Akuntansi dengan Fitur Stok Telur Menggunakan Metode FIFO : Peternakan Ayam Semeru Farm - Christian Adri Wibisono Hartanto; Soetam Rizky Wicaksono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Semeru Farm is a company operating in the chicken farming sector. The main challenge faced by this company is financial management using manual methods with financial recording and reporting through excel applications. This requires accurate calculations in preparing profit and loss reports. In addition, the company also faces obstacles related to egg stock inventory management to ensure freshness and availability when customers buy. To overcome this problem, an accounting information system is needed that integrates stock management using the FIFO (first in first out) method, so that financial recording and reporting can be done efficiently and on time. This study aims to develop an accounting information system that manages egg stock using the FIFO method. This project includes three main phases: analysis, design, and implementation. The results include 38 database tables, transactions covering 5 accounting cycles, and various financial reports such as cash in and out reports, general journals, and final balance sheets.